VARIATION IN ANTIOXIDANT ATTRIBUTES AND INDIVIDUAL PHENOLICS OF CITRUS FRUIT PEELS IN RELATION TO DIFFERENT SPECIES AND EXTRACTION SOLVENTS - Zahoor, Sadaf; Anwar, Farooq; Mehmood, Tahir; Sultana, Bushra; Qadir, Rahman (Journal of the Chilean Chemical Society, 2016)
Major objective of this study was to appraise the variation of antioxidant activity, total phenols, total flavonoids and individual phenolic acids among fruit peels from five species of Citrus namely C. sinensis ‘Valancia’ (Mausami), C. sinensis ‘Maltaise Sanguine’ (Red blood), C. reticulata (Kinnow), C. reticulata Blanco ‘Merisol’ (Fruiter), and C. paradisi ‘Macfadyen’ (Grapefruit) as function of extraction solvents. The extract yield from the fruit peels of the selected Citrus species by using four solvents varied significantly (p<0.05) 17.56-49.13 g/100g in relation to the extraction media and type of peel. The highest extraction yield was obtained with 100% methanol from Red blood (C. sinensis ‘Maltaise Sanguine’) peel while the least with 100% ethanol from Fruiter (C. reticulata Blanco ‘Merisol’) peel. The total phenolic contents (TPC), total flavonoid contents (TFC), DPPH radical scavenging activity (IC50) and reducing power [FRAP (E C50)] for peel extracts ranged from 13.69 to 66.10 GAE mg/g of dry weight (DW), 9.34 to 28.99 CE mg/g DW, 0.33 to 2.32 mg/mL and 2.05 to 6.76 mg/mL, respectively. According to HPLC analysis of peel extracts, gallic acid and protocatechuic acid with contribution 11.96-96.08 and 109.18-578.59mg/kg of extract, respectively, were detected to be the main phenolic acids among others. Total amount of individual phenolic acids (TPAs) in the tested peels varied over 18.37 to 1015.99 mg/kg of extract. The highest amount of TPAs was extracted in Red blood (C. sinensis ‘Maltaise Sanguine’) with 80% methanol while the least in Grapefruit (C. paradisi ‘Macfadyen’) with 100% methanol. It can be concluded from the present data that both the species and extraction solvents have notable effect on the antioxidant attributes and phenolics of citrus peels. Overall, the results of this study showed that extracts from peel of Red blood (C. sinensis ‘Maltaise Sanguine’), among others, possessed superior antioxidant activity and greater amount of phenolic acids.